2020
DOI: 10.1186/s12864-020-06991-3
|View full text |Cite
|
Sign up to set email alerts
|

The GAMYB gene in rye: sequence, polymorphisms, map location, allele-specific markers, and relationship with α-amylase activity

Abstract: Background: Transcription factor (TF) GAMYB, belonging to MYB family (named after the gene of the avian myeloblastosis virus) is a master gibberellin (GA)-induced regulatory protein that is crucial for development and germination of cereal grain and involved in anther formation. It activates many genes including high-molecularweight glutenin and α-amylase gene families. This study presents the first attempt to characterize the rye gene encoding GAMYB in relation to its sequence, polymorphisms, and phenotypic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The previous investigations (Gocal et al 2001 ; Tsuji et al 2006 ) suggest that GAMYB is a part of the central GA pathway, not only in the cereal aleurone layer but also in other plant tissues. This transcription factor (TF) encodes gibberellin-induced regulatory protein that is engaged in plant development and involved, among others, in anther formation (Bienias et al 2020 ). In these organs, HvGAMYB levels are approximately doubled in response to GA3 (Aya et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…The previous investigations (Gocal et al 2001 ; Tsuji et al 2006 ) suggest that GAMYB is a part of the central GA pathway, not only in the cereal aleurone layer but also in other plant tissues. This transcription factor (TF) encodes gibberellin-induced regulatory protein that is engaged in plant development and involved, among others, in anther formation (Bienias et al 2020 ). In these organs, HvGAMYB levels are approximately doubled in response to GA3 (Aya et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…The qPCR genotyping primer design strategy focuses on large deletions, indel insertion/deletion sites or SNP sites of alleles. Meanwhile, mismatched bases can be introduced at the 3′ ends of the primers to improve their resolution [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis and rice, GA can regulate stamen and anther development via the transcriptional regulation of GAMYB. GAMYB is the specific transcriptional regulator of GA, involved in the development of the anther and produced by miRNA159 (Bienias et al ., 2020; Zhang et al ., 2014b).…”
Section: Gibberellin and Male Sterilitymentioning
confidence: 99%
“…The first study of GAMYB was in cereals (Barley) and was found in the aleurone cells, where it was found that GAMYB binds specifically to a GA‐response element in the 5′ regulatory regions of GA‐activated genes (Gubler et al ., 1995). In further study, it was found that GAMYB not only functions in the aleurone cells but also has a role in the cells of the anther (Bienias et al ., 2020). For instance, GAMYB‐4 produces an abnormal (enlarged) tapetum, due to which the normal process of meiosis is disturbed (Liu et al ., 2010).…”
Section: Gibberellin and Male Sterilitymentioning
confidence: 99%